2000
DOI: 10.4049/jimmunol.164.3.1458
|View full text |Cite
|
Sign up to set email alerts
|

IL-13 Is a Susceptibility Factor forLeishmania majorInfection

Abstract: Leishmania major infection is useful as an experimental model to define factors responsible for the development and maintenance of Th cell immune responses. Studies using inbred mouse strains have identified that the Th1 response characteristic of C57BL/6 mice results in healing, whereas BALB/c mice fail to control the infection due to the generation of an inappropriate Th2 response. We now demonstrate that IL-13 is a key factor in determining susceptibility to L. major infection. Overexpression of IL-13 in tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
109
2
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(120 citation statements)
references
References 32 publications
7
109
2
2
Order By: Relevance
“…In infections involving L. major substrain IR173, in which the absence of IL-4R␣ was sufficient to control these parasites, anti-IL-10R treatment caused a further and again striking reduction in the number of parasites in the lesion and draining LN. The idea that IL-4 might act in concert with IL-13 to produce an additive effect on L. major susceptibility has already been supported (20), and the current data extend this concept as it applies to IL-10 and to the cumulative effect of three disease-promoting cytokines.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…In infections involving L. major substrain IR173, in which the absence of IL-4R␣ was sufficient to control these parasites, anti-IL-10R treatment caused a further and again striking reduction in the number of parasites in the lesion and draining LN. The idea that IL-4 might act in concert with IL-13 to produce an additive effect on L. major susceptibility has already been supported (20), and the current data extend this concept as it applies to IL-10 and to the cumulative effect of three disease-promoting cytokines.…”
Section: Discussionsupporting
confidence: 62%
“…While much of the work has focused on IL-4, roles for IL-13 and IL-10 have recently been reported (12,13,20). In previous studies we found that, depending on the L. major substrain, IL-4 KO mice and even IL-4R␣ Ϫ/Ϫ mice deficient in both IL-4 and IL-13 activities remained fully susceptible to L. major.…”
Section: Discussionmentioning
confidence: 90%
“…It has been shown in other studies that IL-4 deficiency was not sufficient to control infection or induce a healing response in BALB/c mice (NobenTrauth, Paul and Sacks 1999; Noben-Trauth, Kropf and Müller 1996). A study confirmed this in different BALB/c lines and parasite strains (Kropf et al 2003 (Matthews 2000). Yet other studies argue that global IL-4Rα knock-out BALB/c mice contain infection in the acute phase but succumb to progressive necrosis in chronic stages of infection, unlike IL-4 deficient counterparts (Sacks and Noben-Trauth 2002;Mohrs et al 1999;Mohrs, Holscher and Brombacher 2000).…”
Section: Il-4rα Signallingsupporting
confidence: 70%
“…Studies in mice using single and double knockouts for IL4 and IL13, and transgenic reintroduction of IL13, indicate an independent role for IL13 in susceptibility to L. major infection. 12 Further studies are in progress using a large number of single nucleotide polymorphisms to fine map the disease causing gene/ mutations across this region of 5q23.3 in this Sudanese population. The corollary to genes regulating type 2 cytokines as candidate susceptibility genes in leishmaniasis are genes causing a defect in the type 1 cytokine pathway.…”
Section: Discussionmentioning
confidence: 99%